Membaca Resitatif sebagai Pendekatan Berorientasi Stabilitas untuk Mengembangkan Otomatisasi Pelafalan pada Pembelajar EFL - Dhoni Tata Priya Pradita; Arif Suryo Priyatmojo (Journal of Education and Teaching Learning, 2026)
Reading in EFL classrooms has increasingly shifted toward interactive and learner-centered approaches; however, contemporary pedagogy often prioritizes novelty and variation over stability and repetition, potentially overlooking essential processes in skill development. This article aims to conceptually examine the role of recitational reading as a stability-oriented pedagogical approach in fostering pronunciation automaticity among high school EFL learners. Adopting a conceptual research design, this study does not involve human respondents but instead synthesizes existing literature and cognitive theories, particularly Skill Acquisition Theory, to explain how repeated and structured oral reading contributes to language development. The analysis highlights that recitational reading, through repeated exposure and oral performance, strengthens the relationship between decoding and phonological processing, reduces cognitive load, and facilitates the gradual emergence of automaticity. Findings from prior studies indicate that reading aloud improves phonological accuracy, reading fluency, and comprehension, while also supporting learners’ confidence and engagement. Furthermore, pronunciation is positioned not merely as an isolated linguistic skill but as a foundational component underlying fluent reading and meaning construction. This study argues that stability, achieved through repetition and guided practice, precedes learners’ ability to process linguistic novelty effectively. Therefore, reading aloud should be reconceptualized as a cognitive-pedagogical mechanism rather than a conventional classroom activity. The study implies that EFL instruction should revalue repetition-based practices as theoretically grounded and pedagogically essential strategies for developing pronunciation automaticity, fluency, and overall reading proficiency.